2002
DOI: 10.1182/blood-2002-05-1372
|View full text |Cite
|
Sign up to set email alerts
|

Mice expressing a neutrophil elastase mutation derived from patients with severe congenital neutropenia have normal granulopoiesis

Abstract: Severe congenital neutropenia (SCN) is a syndrome characterized by an isolated block in granulocytic differentiation and an increased risk of developing acute myeloid leukemia (AML). Recent studies have demonstrated that the majority of patients with SCN and cyclic neutropenia, a related disorder characterized by periodic oscillations in the number of circulating neutrophils, have heterozygous germline mutations in the ELA2 gene encoding neutrophil elastase (NE). To test the hypothesis that these mutations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 50 publications
0
43
0
1
Order By: Relevance
“…Nonetheless, one should not overlook the fact that different species have different metabolic rates, and dynamics proceed with characteristic species' time scales that follow allometric principles [12]. Therefore, and in keeping with this discussion, the conclusion that mutations in ELA2 alone cannot explain CN in a mouse model must be interpreted with caution [13]. Measuring the neutrophil count ev-ery week in mice proves unfortunate, as such a sampling period turns out to be a multiple of the CN cycling period.…”
Section: Resultsmentioning
confidence: 97%
“…Nonetheless, one should not overlook the fact that different species have different metabolic rates, and dynamics proceed with characteristic species' time scales that follow allometric principles [12]. Therefore, and in keeping with this discussion, the conclusion that mutations in ELA2 alone cannot explain CN in a mouse model must be interpreted with caution [13]. Measuring the neutrophil count ev-ery week in mice proves unfortunate, as such a sampling period turns out to be a multiple of the CN cycling period.…”
Section: Resultsmentioning
confidence: 97%
“…This mature 218 amino acid glycoprotein has a critical pathophysiolocial role in a variety of pulmonary disease, including lung cancer [11]. Recently, several studies reported association between mutations in the NE gene and two rare genetic diseases, cyclic neutropenia and severe congenital neutropenia [12][13][14][15][16][17][18][19]. There are 25 single nucleotide polymorphisms (SNPs) listed in the National Center for Biotechnology Information (NCBI)/SNP database (November 10, 2004), 13 of them are validated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is noteworthy that knock-in mice with single ELA2 mutations found in patients do not result in a baseline neutropenia in these animals. 42,43 This implies that effects on multiple granule proteins may be required for this effect in neutrophils. However, to date we have not been able to show that the engineered MBP-1 and EPX loci 16,17 actually generate truncated or aberrant polypeptides (our unpublished observations) and the suggestion that specific events need to coordinately happen in two genes limits the probability of this explanation.…”
Section: Mbp-1/epx-dependent Eosinophilopoiesis 787mentioning
confidence: 99%